2013
DOI: 10.1063/1.4828939
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive interactions of a lipid membrane with graphene in composite materials

Abstract: The van der Waals interaction between a lipid membrane and a substrate covered by a graphene sheet is investigated using the Lifshitz theory. The reflection coefficients are obtained for a layered planar system submerged in water. The dielectric response properties of the involved materials are also specified and discussed. Our calculations show that a graphene covered substrate can repel the biological membrane in water. This is attributed to the significant changes in the response properties of the system du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Graphene‐related nanomaterials are believed to have great potential in applications in the fields of biology and biomedicine (Liu et al, , ; Sanchez et al, ; Sun et al, ; Wang et al, ; Yi and Gao, ), and have been used for biosensors (Ali et al, ; Ang et al, ; Liu et al, ; Qing et al, ), antibacterials (Dallavalle et al, ; Duan et al, ; Li et al, ; Mao et al, ; Pham et al, ; Pykal et al, ; Tu et al, ), bioimaging (Qian et al, ; Shi et al, ; Sun et al, ; Wang et al, ), regulation of cell growth and differentiation (Lee et al, ; Ruiz et al, ). Recently, the interaction between graphene oxide (GO) and cell membranes, including supported lipid bilayers (SLBs), has become the focus of many researchers (Frost et al, ; Furukawa and Hibino, ; Lei et al, ; Li et al, a,b; Okamoto et al, ; Phan et al, ; Rui et al, ; Wu et al, ) not only because cell membrane is the first barrier when GO interacts with intracellular components, but also it can provide us valuable information on physicochemical nature of GO. In terms of the structure, GO is a highly oxidized form of graphene, which retains the hydrophobic sp2‐hybridized domains, as well as the hydrophilic sp3‐hybridized groups including C–OH, C–O–C, and –COOH (Andre Mkhoyan et al, ; Boukhvalov and Katsnelson, ; Dreyer et al, ; Erickson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Graphene‐related nanomaterials are believed to have great potential in applications in the fields of biology and biomedicine (Liu et al, , ; Sanchez et al, ; Sun et al, ; Wang et al, ; Yi and Gao, ), and have been used for biosensors (Ali et al, ; Ang et al, ; Liu et al, ; Qing et al, ), antibacterials (Dallavalle et al, ; Duan et al, ; Li et al, ; Mao et al, ; Pham et al, ; Pykal et al, ; Tu et al, ), bioimaging (Qian et al, ; Shi et al, ; Sun et al, ; Wang et al, ), regulation of cell growth and differentiation (Lee et al, ; Ruiz et al, ). Recently, the interaction between graphene oxide (GO) and cell membranes, including supported lipid bilayers (SLBs), has become the focus of many researchers (Frost et al, ; Furukawa and Hibino, ; Lei et al, ; Li et al, a,b; Okamoto et al, ; Phan et al, ; Rui et al, ; Wu et al, ) not only because cell membrane is the first barrier when GO interacts with intracellular components, but also it can provide us valuable information on physicochemical nature of GO. In terms of the structure, GO is a highly oxidized form of graphene, which retains the hydrophobic sp2‐hybridized domains, as well as the hydrophilic sp3‐hybridized groups including C–OH, C–O–C, and –COOH (Andre Mkhoyan et al, ; Boukhvalov and Katsnelson, ; Dreyer et al, ; Erickson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al concluded that the hemolytic activity of both GO and graphene damaged skin fibroblasts and human erythrocytes . Generally, GO sheets may encounter a cell membrane first when it is presented in a cell culture medium, and the interaction between GO and cell membranes has become the focus of much research. ,, Therefore, systems containing GO and liposomes or solid-supported lipid bilayers are widely investigated either theoretically or experimentally as convenient and direct models. For instance, Frost et al reported that GO and lipid membranes can generate an altering multilayer structure through electrostatic interactions between GO and lipid headgroups .…”
Section: Introductionmentioning
confidence: 99%
“…Liu’s group systematically studied the interaction of GO with liposome and found that liposome can be absorbed on the side of GO; accordingly, a drug-delivery system was designed. , Furukawa et al reported that supported lipid bilayers (SLBs) cannot spread to the GO . By using molecular simulation methods, researchers have revealed on the molecular level that electrostatic and hydrophobic forces are the main interactions between GO and lipid membranes. , …”
Section: Introductionmentioning
confidence: 99%
“…These systems are especially appealing since graphene possesses unique mechanical, electrical, and optical properties [25]. Recently, dispersive interactions between graphene sheets and/or material planes have been investigated [26][27][28][29][30][31][32][33][34][35][36][37][38][39], as well as the Casimir-Polder interaction between atoms and graphene [40][41][42][43][44][45]. In particular, the impact of a graphene coating on the atom-plate interaction has been calculated for different atomic species and substrates; in some cases this results in modifications of the order of 20% in the strength of the interaction [44].…”
mentioning
confidence: 99%